The Effect of the Direct Instruction Learning Model on Student Learning Outcomes on Theme 3 Healthy Food at Class V of State Primary School - Gaol, Endang Lumban; Silaban, Patri Janson; Sitepu, Anton; Abi, Antonius Remigius; Ambarwati, Nova Florentina (JURNAL PAJAR (Pendidikan dan Pengajaran), 2024)
This paper discusses the effect of the direct instruction learning model on student learning outcomes on theme 3 Healthy Food at class V of SD Negeri 173418 Pollung in the academic year 2023/2024. The research method used was an experimental method with a one-group pretest-posttest research design. The research sample involved 30 students. Data collection tools used to determine student learning outcomes were question instruments and questionnaires, which were tested for validation and reliability. The average value of learning outcomes obtained during the pretest was 46,4. After that, students were given treatment using the direct instruction learning model. It, in addition, indicated an average score on the post-test with a score of 86. It can be seen that the pre-test and post-test learning outcomes have increased. The data analysis used comes from the normality test. It is known that the results obtained are Lcount 0.200 ≥ Ltable 0.161, which can be said to be normally distributed. Of the correlation coefficient test, the results indicate rcount 0.811 ≥ rtable 0.361 with the interpretation of the r value obtained in the range 0,800 – 1,000. It can be said that there is a very high relationship between the effect of the direct instruction learning model and the learning outcomes of students in class V. Based on the hypothesis test statistical results obtained with tcount 7.333 ≥ ttable 2.048 or significant value 0.000 ≤ 0.05. So, Ha is rejected, which means that there is an effect of the direct instruction learning model on student learning outcomes.